The relationship between polypharmacy and the incidence of drug interactions in pediatric inpatients at the regional general hospital (RSUD) Embung Fatimah Batam city - Wahyudi; Nurmesa, Adi (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2025)
Polypharmacy is one of the risk factors for potential drug interactions that can cause unwanted drug reactions and can also increase the risk to pediatric patients. This study aims to see if there is a relationship between polypharmacy and the incidence of drug interactions in pediatric inpatient prescriptions that will be carried out at Embung Fatimah Regional General Hospital, Batam City. This study uses a cross-sectional method, an observational research design conducted to determine the relationship between polypharmacy as the independent variable and the incidence of drug interactions as the dependent variable, with measurements taken at a single point in time. The target population to be studied is the total number of inpatient pediatric prescriptions at Embung Fatimah Hospital as many as 440 prescriptions. The sample used in this study was taken from the affordable population with inclusion and exclusion criteria. Polypharmacy prescriptions for pediatric inpatients at Embung Fatimah Regional General Hospital (RSUD) Batam City based on the results of research from a total of 168 prescriptions there were 123 (73.2%) polypharmacy prescriptions and 45 non-polypharmacy prescriptions. Drug interactions in pediatric inpatient prescriptions at the Regional General Hospital (RSUD) Embung Fatimah Batam City based on the results of the study from a total of 168 prescriptions there were 44 prescriptions experiencing drug interactions and 124 did not experience drug interactions. There is a significant relationship between polypharmacy and the incidence of drug interactions in pediatric inpatients at Embung Fatimah Regional General Hospital (RSUD) Batam City. The Chi-Square test resulted in a P-value ≤ 0.05, indicating that the null hypothesis (H₀), which states that there is no relationship between polypharmacy and drug interactions, is rejected. Consequently, the alternative hypothesis (H₁), which states that polypharmacy is significantly associated with the incidence of drug interactions, is accepted.